Hubungan Higiene Sanitasi terhadap Kepuasan Pasien Rawat Inap pada Pelayanan Makanan di Rumah Sakit - Aprilia, Mochthalifah; Fauziah, Lilia Faridatul; Ristanti, Idcha Kusma (Media Gizi Ilmiah Indonesia, 2025)
Satisfaction is a person's feeling of pleasure or disappointment after comparing the perceived performance results with their expectations. The purpose of this study was to analyze the relationship between sanitation hygiene and inpatient satisfaction with food services at NU Tuban Hospital. The research design us ed was correlational analytic with a cross-sectional approac h. The type of research was quantitative and the instrument used was a questionnaire. Data analysis used the Spearman Rank Correlation test. The results showed that there was a relationship between sanitation hygiene and inpatient satisfaction with food services with a p value = 0.000. The conclusion of this study is that the better the sanitation hygiene, the better the food service at NU Tuban Hospital. Patient satisfaction with food services at NU Tuban Hospital has met the standards.